Use of roleplay and community engagement to teach parasitic diseases - Firoza Haffejee; Jacqueline van Wyk; Varsha Hira (South African Medical Association, 2017)
Background. Role-play can enhance students’ learning, improve communication and serve as an effective tool for team building. When combined with community engagement projects (CEPs), it can enhance empathy in challenges relating to the community. The benefits of role-play in medical education have been reported, but the impact of the strategy is unknown in the allied health sciences at universities of technology, where there is a need to improve pass rates.Objective. To ascertain the benefits of role-play and CEPs in the context of understanding parasitic diseases by students enrolled for programmes in the allied health professions.Method. Role-play and CEPs were used to facilitate students’ learning of parasitic diseases. Students’ perceptions of the influence of these strategies on their learning were determined through the use of a semi-structured questionnaire. Test scores of the students before and after the assignment were compared.Results. The majority of students reported becoming more enthusiastic about their studies. They indicated that role-play with regard to the clinical features of the parasitic diseases added to their improved understanding of the disorders. Role-play also made the learning entertaining and informative, and enhanced class camaraderie. An improvement in the students’ test marks and pass rates relating to this section was also observed. Students valued the opportunity to teach people in the community, which linked their learning to a community engagement initiative.Conclusion. Learning through role-play and using a CEP to teach about parasites enhanced the quality of student learning in the allied health sciences.